Aerobic Isolates from Gestational and Non-Gestational Lactating Bitches (Canis lupus familiaris) - Iosif Vasiu; Gabriele Meroni; Roman Dąbrowski; Piera Anna Martino; Asta Tvarijonaviciute; Mariola Bochniarz; Raul Alexandru Pop; Florinel Gheorghe Brudaşcă; Nicodim Iosif Fiţ (Animals, 2021)
Mastitis is a complex and well-defined mammary gland pathology, and an emergency in bitches. In dogs, its prevalence is about 1% of all reported diseases and about 5.3% of all reproductive pathologies. Lactating bitches are naturally prone to developing mastitis since puppies can easily overstimulate the epidermal layer of nipples during feeding, facilitating bacterial colonization of the glands. This study aimed to describe the aerobic bacterial flora isolated from milk samples derived from a cohort of patients (n = 87) diagnosed with clinical mastitis (n = 29), subclinical mastitis (n = 17) and healthy mammary glands (n = 46). All of the patients underwent a gynecology consultation to diagnose mammary gland afflictions; physical examination results were coupled with traditional hematological findings. The milk samples were plated on specific microbiological media for bacterial isolation. Among the 162 milk samples analyzed, 93.2% (151/162) had a positive microbiological result, while 6.8% (11/162) were sterile. The bacteriological profile of the milk samples showed 47 different species. The most common bacterial families detected in healthy bitches and bitches with subclinical and clinical mastitis were the Staphylococcaceae, Enterobacteriaceae and Enterococcaceae families. The results indicated that half of the isolated bacteria are novel findings in dogs and that some of them are normal components of human milk.